Data Politics: Worlds, Subjects, Rights - Bigo, Didier; Isin, Engin F. (Engin Fahri); Ruppert, Evelyn Sharon (Routledge Studies in International Political Sociology, 2019)
Data has become a social and political issue because of its capacity to reconfigure relationships between states, subjects, and citizens. This book explores how data has acquired such an important capacity and examines how critical interventions in its uses in both theory and practice are possible. Data and politics are now inseparable: data is not only shaping our social relations, preferences and life chances but our very democracies. Expert international contributors consider political questions about data and the ways it provokes subjects to govern themselves by making rights claims. Concerned with the things (infrastructures of servers, devices, and cables) and language (code, programming, and algorithms) that make up cyberspace, this book demonstrates that without understanding these conditions of possibility it is impossible to intervene in or to shape data politics. Aimed at academics and postgraduate students interested in political aspects of data, this volume will also be of interest to experts in the fields of internet studies, international studies, Big Data, digital social sciences and humanities. The Open Access version of this book, available at https://www.routledge.com/Data-Politics-Worlds-Subjects-Rights/Bigo-Isin-Ruppert/p/book/9781138053267, has been made available under a Creative Commons Attribution-Non Commercial-No Derivatives 4.0 license.